Herpes simplex virus type 1 and type 2 in the Netherlands: seroprevalence, risk factors and changes during a 12-year period. Issue 1 (December 2016) - Woestenberg, Petra; Tjhie, Jeroen; de Melker, Hester; van der Klis, Fiona; van Bergen, Jan; van der Sande, Marianne; van Benthem, Birgit
Abstract Background Genital herpes results in considerable morbidity, including risk of neonatal herpes, and is increasingly being caused by Herpes Simplex Virus (HSV) type 1. Possibly children are less often HSV-1 infected, leaving them susceptible until sexual debut. We assessed changes in the Dutch HSV-1 and HSV-2 seroprevalence over time and determinants associated with HSV seropositivity. Methods We used data from two population-based seroepidemiological studies conducted in 1995–6 and 2006–7 with a similar study design. Serum samples of 6 months to 44-year-old participants were tested for type-specific HSV antibodies using HerpesSelect® with a cut-off level of >1.10 for seropositivity. Age and sex-specific HSV-1 and HSV-2 seroprevalence was weighted for the Dutch population. Logistic regression was performed to investigate determinants associated with HSV seropositivity. Results Overall, weighted HSV-1 seroprevalence was significantly lower in 2006–7 [42.7 % 95 % confidence interval (CI) 39.9-45.4] than in 1995–6 (47.7 % 95 % CI 44.8-50.7), especially among 10- to 14-year-olds. Overall, weighted HSV-2 seroprevalence remained stable: 6.8 % in 1995–6 and 6.0 % in 2006–7. Adults who ever had sexual intercourse were more often seropositive for HSV-1 [adjusted Odds Ratio (aOR) 1.69 95 % CI 1.33-2.16] and HSV-2 (aOR 2.35 95 % CI 1.23-4.52). Age at sexual debut was the only sexual risk determinant associated with HSV-1 seropositivity. Conclusions Because of the lower HSV-1 seroprevalence in 2006–7 compared to 1995–6, more adults are susceptible to genital HSV-1, including women of reproductive age. Given the higher risk of neonatal herpes when HSV is acquired during pregnancy, prevention and control measures during pregnancy also targeting HSV-1, are important.